Adaptation study of the Texas Revised Inventory of Grief - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2011)
Objective: To establish validity and reliability of the Texas Revised Inventory of Grief (TRIG) in Turkish population. Methods: One hundred and fifty-four parents whose infants deceased in the Neonatal Intensive Care Unit of a public hospital formed the sample. The data were collected using TRIG. TRIG was developed by Faschingbauer et al. the measure the intensity of the grief reaction following loss of a loved one. The inventory includes 21 items and two sections. Adaptation of the TRIG to the Turkish included back-translation of the inventory and its lingual and content validity were established by 14 specialists. The 20 items were approved for baby loss. TRIG was applied with 154 parents through telephone calls three months after the death of their infants. The collected data were evaluated by confirmatory factor analysis, 27% extreme-group method, Pearson moments multiplication correlation analysis and Cronbach's alpha analysis. Results: The results obtained by the confirmatory factor analysis showed the factor patterns for mother and fathers were in accordance with the original inventory. For internal consistency, Cronbach's a was 0.85, item-total score reliability was 0.28 and 0.37 in two questions, and within the 0.44-0.66 range in others, item-subpart total score reliability ranged between 0.44-0.72 for the 'past behaviors' part I and between 0.39 and 0.74 for the 'present emotional feeling' part II. The correlation coefficient calculated for the scale-subpart was 0.82 for 'past behaviors' part I and 0.94 for 'present emotional feeling' part II. Conclusion: The Turkish version of the TRIG is a valid and reliable inventory to evaluate the intensity of grief reaction experienced after loss of a loved one. (Anatolian Journal of Psychiatry 2011; 12:30-36)
Keywords: grief process; loss of loved one; inventory; reliability; validity; BEREAVEMENT; DEATH; VALIDATION; INFANTS; CANCER; LIFE